DEMOGRAFICZNE ASPEKTY PROCESU STARZENIA SIĘ LUDNOŚCI POLSKI - Wierzchosławski, Stanisław (Wydział Prawa i Administracji UAM, 1999)
The paper discusses the attempt undertaken for to review demographic conditions of the ageing process of the Polish population, as well as for to get to know the mechanism of this process and to formulate next a diagnosis of the present state and, finally, to determine a perspective of development of this process in relation with long-term prognoses. The study is preceded with a comment on general trend of the ageing of populations in Western Europe countries where this process has begun much earlier as a result of advanced demographic transformations in these countries and, consequently — deep changes within the populations. The process of the ageing causes serious changes in the structure of the population age; the changes are considered in relatively long time section and on a basis of retrospective estimations as well as projections made by the Population Department of the UN (1950 - 2050). The process of the ageing leads to a deformation of the so-called principle of „age structure balance” as formulated by G. Sundbàrg; this fact causes a demographic revolution the expression of which is the replacement of „natural balance” with „rational balance”. Such a new situation produces a series of consequences and implications in demographic processes known up to the present. The process of the population ageing is inevitably accompanied with a depopulation process - including all its consequences. The Author considers - sifter Italian demographer A. Golini - the rapidity and intensity of the process of a demographic ageing of the population in Poland and other European countries. The groundwork for these considerations is the period where the population of young people (Lo-19) gets equal to the population of the elderly (L60+). Much attention is paid by the Author to the mechanism of the population ageing in Poland during the XlXth and XXth centuries as well as to the perspective of the mid-XXIst century; the same attention is also paid to looking for an answer to the following question: if our country, similarly to other European societies, shall be able to stand up to numerous challenges resulting from the processes of demographic modernisation and from the ageing of the population?
DEMOGRAPHIC ASPECTS OF THE AGEING PROCESS OF THE POPULATION IN POLAND